Formulasi Granul Mukoadhesif Ketoprofen Menggunakan Polimer Kitosan - Salman Umar; Wida Ningsih; Monalisa Meliana (Jurnal Sains Farmasi & Klinis, 2014)
The aim of this research was to formulate of mucoadhesive ketoprofen granules using chitosan polymer. Ketoprofen granules were prepared by wet granulation method with several concentrations of chitosan polymer 0%, 10%, 20%, and 30% (w/v). Granules were evaluated physically and chemically. In vitro dissolution test was carried out for 6 hours using a basket method in buffer phosphate medium pH 7.4. General evaluation of granules showed the yield was relatively good. In vitro mucoadhesive test exhibited that mucoadhesive ketoprofen granules using chitosan polymer could provide mucoadhesive properties to stomach and intestinal of rabbits. The statistics tests for dissolution efficiency with one ways ANOVA (SPSS 17) showed a significant different among F0, F1, F2 and F3 (P0.05). All the formulas followed Langenbucher kinetic release model.